Development of innovative industries in Russia under unfavourable external environment; Equilibrium. Quarterly Journal of Economics and Economic Policy; Vol. 13, No. 3 - Spitsin V. V. Vladislav Vladimirovich; Mikhalchuk A. A. Aleksandr Alexandrovich; Chistyakova N. O. Natalya Olegovna; Spitsyna L. Yu. Lubov Yurievna; Pavlova I. A. Irina Anatolievna (2018, 2018)
Title screen